A reflexão teológica no meio universitário - Correia Júnior, João Luiz (Revista eclesiástica brasileira, 2002)
The University and, in a wide-angle view, the university culture lends important service in scientific and technological development, as well as in fomenting cultural expressions in the region in which it is included. In what way can Theoloo, critical æflection on thefundamental values of life, in the light of faith, contribute to the formation of university culture, within the serious challenges of the present?